TACTICAL AND PROCEDURAL FEATURES OF INTERROGATION OF A VICTIM DURING THE INVESTIGATION OF CRIMINAL OFFENSES PROVIDED FOR BY ARTICLE 156-1 OF THE CRIMINAL CODE OF UKRAINE (Bulletin of criminological association of Ukraine, 2025)
The article investigates the tactical and procedural features of interviewing victims during the investigation of criminal offenses stipulated in Article 156-1 of the Criminal Code of Ukraine, which is one of the most complex and sensitive categories of crimes. It emphasizes that interviewing child victims significantly differs from interviewing adults and requires a profound understanding of child developmental psychology. The necessity of an individualized approach to studying the personality of the interviewee is highlighted, specifically through preliminary communication with the child involving a psychologist and conducted in an informal setting. It is noted that this approach allows for identifying the child's psychotype, emotional and psychological state, level of physiological and psychological development, as well as their willingness to cooperate. Particular attention is paid to assessing the degree of psychological trauma and risks of retraumatization during investigative actions, which is a priority in investigating such crimes. The article elaborates on tactical techniques aimed at ensuring the child's trust and comfort, such as creating a favorable atmosphere, using accessible language, and avoiding leading or traumatizing questions. Emphasis is placed on selecting the appropriate moment for the interview and minimizing its duration. Procedural requirements for recording the child’s interview are described. In addition to traditional protocoling, the importance and necessity of video recording as the primary method of documenting testimony are emphasized. In this context, the practical value and legal aspects of using the "Green Room" methodology or the "Barnahus" model are examined.
Keywords: forensic methodology; sexual exploitation; sexual violence, investigation methodology; child grooming; interview tactics; victim; Barnahus model